Cerebral Insufficiency Caused by Diazoxide in a Premature Neonate with Congenital Hyperinsulinism - Okada, Seigo; Fukunaga, Shinnosuke; Ohta, Haruka; Furuta, Takashi; Hirano, Reiji; Motonaga, Takahiro; Ishikawa, Yuichi (Neuropediatrics, 2020)
Diazoxide is a peripheral vasodilator that has been used for intravenous treatment of hypertensive emergencies. However, it is currently used mainly for hyperinsulinemic hypoglycemia in lower dose orally, and its major side effects are edema and pulmonary hypertension. Herein, we report the first association between periventricular leukomalacia (PVL) and intractable hypotension due to diazoxide. A Japanese female premature infant showed hypoglycemia concomitant with hyperinsulinemia. She was diagnosed with congenital hyperinsulinism, and oral diazoxide was started. Six days after starting diazoxide, she suddenly showed peripheral coldness, oliguria, and severe hypotension. The hypotension was refractory to general vasopressor therapies and persisted even after the discontinuation of diazoxide. Cranial echography showed periventricular echodensities followed by cystic PVL. Low-dose vasopressin effectively treated the hypotension. This single case reminds us the serious adverse events of diazoxide that have been forgotten, especially in premature neonates.
Keywords: hypoglycemia; neonate; periventricular leukomalacia; vasodilator